PENGARUH PENGETAHUAN INVESTASI SAHAM DAN MOTIVASI BERINVESTASI SAHAM TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL PADA MAHASISWA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI MANADO - Adeleida Joroh; Rolyke Tulangow (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2020)
Stocks Investing is not someting common today, this supported by increasingly rapid development of technology. People can get data anywhere at any time, we can even transact stock using smartphone. this study aims: To find out how the influence of investment motivation on the interest in investing in stocks in the capital market of students of the Business Management Study Program, Departemen of Business Administration, Manado State of Polytechnic. to find out how the influence of knowledge of stock investment and the motivation of investing in stocks on students are interest in investing in the capital market of study program students business management, Departemen of Business Administration, Manado State of Polytechnic. the population in this study are some of the students in the Business Management Study Program. So the author takes a sample of all final semester students in Business Management Study Program. The data used in this study are primary data, so the researcher will collect the data using a quistionnaire. The collected data will be analyzed using statistics to test the hypotesis that has been proposed. The data analysis technique used is simple regression analysis using computer assistance with the SPSS program. Through this research, it is hoped that the research objectives will be answered, with knowledge gained from attending a practical course on portfolio investment and being motivated by investment motivation to spur student interest in investing in stocks. From the correlation analysis, it is known that there is a positive and significant relationship between the variable investement knowledge and investemen interest with a strong relationship category. Likewise, with the investment motivation variabel, there is a positive and significant relationship between investment motivation and investmen interest with a strong category of investmen interest . From the hypothesis test, it is known that all hypoteses are accepted by emperical evidence that the t-value is greater than t-table.